1989
DOI: 10.1038/jcbfm.1989.4
|View full text |Cite
|
Sign up to set email alerts
|

Fructose-1,6-Bisphosphate Protects Astrocytes from Hypoxic Damage

Abstract: Summary:To determine the effects of glucose and fruc tose-l,6-bisphosphate (FDP) on hypoxic cell damage, pri mary cultures of astrocytes were incubated for 18 h in an air-tight chamber that had been flushed with 95% N2/5% CO2 for 15 min before it was sealed. Cultures containing 7. 5 mM glucose without FDP or FDP without glucose showed evidence of significant cell injury after 18 h of hypoxia (increased lactate dehydrogenase content in the culture medium; cell edema and disruption by phase contrast microscopy).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 18 publications
1
22
1
Order By: Relevance
“…No protective effect was observed with any of the additions (data not shown). The lack of protective effect of fructose-l,6-diphosphate is unlike observations made with fully differentiated astrocytes (39).…”
Section: Effect Of Glucose On Hypoxia-induced Ldh Djuxcontrasting
confidence: 56%
“…No protective effect was observed with any of the additions (data not shown). The lack of protective effect of fructose-l,6-diphosphate is unlike observations made with fully differentiated astrocytes (39).…”
Section: Effect Of Glucose On Hypoxia-induced Ldh Djuxcontrasting
confidence: 56%
“…1), reducing mortality during the ischemic period and the earlier phase of recirculation, but exerting only a modest protection against the overall mortality after 8 days of recirculation (i.e., when the histological damage was quantified). All these results appear to agree with some previous observa tions (11,12,15,16). When comparing, however, the results of the present study with others, a couple of fac tors should be considered.…”
Section: Resultssupporting
confidence: 92%
“…Conversely, studies based on [14C]FBP uptake in erythrocytes demonstrated that the compound does not enter the cell (17,18). Fur thermore, no evidence has been provided until now that FBP is taken up by brain cells, although recently, in an experiment conducted on isolated cortical astrocytes in vitro, a rapid incorporation of FBP into cells has been reported (11). Moreover, this phenomenon seems to be energy-dependent since it decreased by nearly 70076 when the temperature was reduced from 37 to 01C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 -2641 - 43 Recently, Gregory et al 43 reported that FDP protects astrocytes subjected to 18 hours of normothermic anoxia. In addition, these authors measured the uptake of radiolabeled FDP and found it to be rapidly incorporated into the cell fraction of normoxic astrocytes.…”
Section: Figure 3 Electroencephalograms (Eegs) Before (Control) and mentioning
confidence: 99%